2019
DOI: 10.1634/theoncologist.2018-0789
|View full text |Cite
|
Sign up to set email alerts
|

Complete Blood Count Score Model Integrating Reduced Lymphocyte-Monocyte Ratio, Elevated Neutrophil-Lymphocyte Ratio, and Elevated Platelet-Lymphocyte Ratio Predicts Inferior Clinical Outcomes in Adult T-Lymphoblastic Lymphoma

Abstract: Background T‐lymphoblastic lymphoma (T‐LBL) is a highly aggressive neoplasm of lymphoblasts of T‐cell origin. Although promising improvements have been recently achieved, one third of patients experience relapse or refractory T‐LBL. Therefore, optimal strategies for identifying high‐risk patients are urgently needed. Materials and Methods In the present study, 75 newly diagnosed adult patients (aged ≥15 years) with T‐LBL were identified and the predictive value of complete blood count (CBC) abnormalities, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
(36 reference statements)
3
25
0
Order By: Relevance
“…In our previous studies, we found some prognostic clinical indicators in T-LBL (14,15). We also found that the novel mutation in CDC27, which ranked highly in the samples (16).…”
Section: Introductionsupporting
confidence: 51%
“…In our previous studies, we found some prognostic clinical indicators in T-LBL (14,15). We also found that the novel mutation in CDC27, which ranked highly in the samples (16).…”
Section: Introductionsupporting
confidence: 51%
“…In line with our results, a number of recently published studies suggest that post-treatment PBC parameters are associated with outcomes of cancer patients after RT or immunotherapy [29][30][31][32][33][34][35]. Barbetta shows that integrating multiple PBC parameters could predict the survival of patients with adult Tlymphoblastic lymphoma [38]. Thus, combining multiple PBC parameters through appropriate integration may reveal their predictive power.…”
Section: Discussionsupporting
confidence: 88%
“…We found that the median PFS for low-risk, intermediate-risk and high-risk groups were 24 ((12.458–35.542), 17 (10.626–23.374), and 9 (8.893–19.107) months, respectively ( p = 0.011), and the median OS were 33 (19.175–46.825), 18 (16.368–19.632), and 9 (6.521–11.479) months, respectively ( p = 0.008), indicating that patients in the high-risk group had a significantly inferior prognosis. In a previous retrospective study of adults with T-lymphoblastic lymphoma, a similar CBC score model consisting of lymphocyte-monocyte ratio, NLR, and PLR was evaluated, and it was found that the median PFS for the low-risk, intermediate-risk, and high-risk groups was not reached, 16 months, and 7 months, respectively ( p = 0.004), whereas the median OS for these three groups was not reached, 46 months, and 20 months, respectively ( p = 0.007) ( 29 ). These findings were consistent with ours, indicating that CBC score model is valuable in predicting PCNSL patient’s prognosis.…”
Section: Discussionmentioning
confidence: 99%